The Impact of Excessive Exercise on the Physical Health of University Students: A Systematic Literature Review (SLR) - Syarief Alwi Assegaf (UNIVERSITAS NEGERI MAKASSAR, 2024)
Sport is an activity that supports physical and mental health. However, excessive exercise can have a negative impact on health, especially for students who often have an unbalanced lifestyle. This article aims to examine the relationship between excessive exercise and its impact on students' physical health through the Systematic Literature Review (SLR) method. In this article it can be concluded that excessive exercise can have a significant impact on students' physical health, including fatigue, physical injury, sleep disorders, and a decrease in the immune system. Therefore, a more balanced approach is needed in designing sports programs for students, as well as awareness of physical limitations to prevent the negative impacts of excessive physical activity.